Design, Development And The Effects Of Emotionally Sound Web-Based Instruction On Performance, Satisfaction, Engagement And Retention - Rasalingam, Rasslenda-Rass (2018)
This study was designed to investigate the effectiveness of the emotionally sound web-based instruction on performance, satisfaction, engagement and retention in learning English grammar among students with different levels of emotional intelligence. The sample consisted of 183 Form Two students from a secondary school in the Northern region of the Peninsular Malaysia. The data were collected with the Trait Emotional Intelligence Questionnaire - Short Form (TEIQue-SF), End-User Computing Satisfaction (EUSC), Post-Test 1, Retention Questionnaire (Post-Test 2) and E-Learning Engagement Instrument (ELEI). The research design for this study is Quasi-experimental with pre-test and post-test design.